Addressing Patient Safety Hazards Using Critical Incident Reporting in Hospitals: A Systematic Review. Issue 1 (20th January 2023) - Goekcimen, Ken; Schwendimann, René; Pfeiffer, Yvonne; Mohr, Giulia; Jaeger, Christoph; Mueller, Simon
Abstract : Introduction: Critical incident reporting systems (CIRS) are in use worldwide. They are designed to improve patient care by detecting and analyzing critical and adverse patient events and by taking corrective actions to prevent reoccurrence. Critical incident reporting systems have recently been criticized for their lack of effectiveness in achieving actual patient safety improvements. However, no overview yet exists of the reported incidents' characteristics, their communication within institutions, or actions taken either to correct them or to prevent their recurrence. Our main goals were to systematically describe the reported CIRS events and to assess the actions taken and their learning effects. In this systematic review of studies based on CIRS data, we analyzed the main types of critical incidents (CIs), the severity of their consequences, their contributing factors, and any reported corrective actions. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we queried MEDLINE, Embase, CINAHL, and Scopus for publications on hospital-based CIRS. We classified the consequences of the incidents according to the National Coordinating Council for Medication Error Reporting and Prevention index, the contributing factors according to the Yorkshire Contributory Factors Framework and the Human Factors Classification Framework, and all corrective actions taken according to an action hierarchy model on intervention strengths. Results: We reviewed 41 studies, which covered 479, 483 CI reports from 212 hospitals in 17 countries. The most frequent type of incident was medication related (28.8%); the most frequent contributing factor was labeled "active failure" within health care provision (26.1%). Of all professions, nurses submitted the largest percentage (83.7%) of CI reports. Actions taken to prevent future CIs were described in 15 studies (36.6%). Overall, the analyzed studies varied considerably regarding methodology and focus. Conclusions: This review of studies from hospital-based CIRS provides an overview of reported CIs' contributing factors, characteristics, and consequences, as well as of the actions taken to prevent their recurrence. Because only 1 in 3 studies reported on corrective actions within the healthcare facilities, more emphasis on such actions and learnings from CIRS is required. However, incomplete or fragmented reporting and communication cycles may additionally limit the potential value of CIRS. To make a CIRS a useful tool for improving patient safety, the focus must be put on its strength of providing new qualitative insights in unknown hazards and also on the development of tools to facilitate nomenclature and management CIRS events, including corrective actions in a more standardized manner.